Efavirenz-Based Antiretroviral Therapy Among Nevirapine-Exposed HIV-Infected Children in South Africa: A Randomized Clinical Trial - Coovadia, Ashraf (JAMA, 2015)
IMPORTANCE: Advantages of using efavirenz as part of treatment for HIV-infected children include once-daily dosing, simplification of co-treatment for tuberculosis, preserving ritonavir-boosted lopinavir for second-line treatment, and harmonization of adult and pediatric treatment regimens. However, there have been concerns about possible reduced viral efficacy of efavirenz in children exposed to nevirapine for prevention of mother-to-child transmission (PMTCT). OBJECTIVE: To evaluate whether nevirapine-exposed children, initially virally-suppressed on ritonavir-boosted lopinavir-based therapy, can transition to efavirenz-based therapy without risk of viral failure. DESIGN, SETTING, PARTICIPANTS: Randomized, open-label, non-inferiority trial conducted at Rahima Moosa Mother and Child Hospital, Johannesburg, South Africa, June 2010 to December 2013. Three hundred HIV-infected children exposed to nevirapine for PMTCT, ≥ 3 years of age, and with plasma HIV RNA <50 copies/ml on ritonavir-boosted lopinavir-based therapy were enrolled; 298 were randomized, and 292 (98%) were followed to 48 weeks post-randomization. INTERVENTION: Switch to efavirenz-based therapy (n=150) or continue on ritonavir-boosted lopinavir-based therapy (n=148). MAIN OUTCOMES AND MEASURES: Risk difference (delta) between groups in (1) viral rebound; i.e., one or more HIV RNA >50 copies/ml, and (2) viral failure; i.e., confirmed HIV RNA >1000 copies/ml; with a non-inferiority bound for the delta of −0.10. Immunologic and clinical responses were secondary endpoints. RESULTS: The Kaplan-Meier probability of viral rebound by 48 weeks was 0.176 (n=26) in the efavirenz group and 0.284 (n=42) in the ritonavir-boosted lopinavir group. Probabilities of viral failure were 0.027 (n=4) in the efavirenz and 0.020 (n=3) in the ritonavir-boosted lopinavir group. The risk difference of viral rebound was 0.107 (1-sided 95% CI: 0.028,∞) and −0.007 (1-sided 95% CI: −0.036, ∞) for viral failure. We rejected the null hypothesis that efavirenz is inferior to ritonavir-boosted lopinavir (p<.001) for both endpoints. By 48 weeks, CD4 percentage was 2.88 (95% CI: 1.26, 4.49) units higher in the efavirenz than in the ritonavir-boosted lopinavir group. CONCLUSIONS AND RELEVANCE: Among HIV-infected children exposed to nevirapine for PMTCT and initially virally-suppressed on ritonavir-boosted lopinavir-based therapy, switching to efavirenz-based therapy compared with continuing ritonavir-boosted lopinavir-based therapy did not result in significantly higher rates of viral rebound or viral failure. This therapeutic approach may offer advantages in children such as these.